The Effect of Climate Change on the Productivity and Profitability of Cod in the Barents Sea - Yaah Jingla, Atanga Forgiveness (UiT The Arctic University of Norway, 2019)
Climate change has an inevitable natural impact on fisheries. Continually, several models made of both biological and economic factors are used to measure the effects of climate change on fish stocks. This study has as its objective to identify how climate change effect through carrying capacity affects the productivity and profitability of the cod stock in the Barents Sea. Two scenarios one with climate change effect and the other without climate change effect are compared to explore the climate change effect. This thesis uses a simple bioeconomic model based on a surplus production model to conduct the analysis over 50 years. Two different vessels are considered, coastal fishing vessels and ocean going vessels. The results suggest the positive effect of climate change on total biomass, harvests and discounted profit for both vessel groups. The results also suggest a bigger effect on the coastal vessels than on the ocean ongoing vessels. Sensitivity analysis suggests noticeable impacts with increase in price and intrinsic growth rate. Although this exercise is rather simple, the findings can be used to improve management measures so as to sustainably exploit fish resources if climate change takes places as anticipated.